European Dimension of Constitutionof the French Fifth Republic - Chodorowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The French doctrine assumes that the Constitution of the Fifth Republic of France is monistic in nature with the primacy of internal law over the EU one. This would mean that constitutional supremacy is indisputable, as everything derives from the constitution, including the authority of EU law in the internal legal order. Thanks to the interpretation of the Constitutional Council, in particular regarding Art. 88-1 of the Constitution, made it possible to overcome a potential conflict between the constitutional norm and EU law, making the primacy of European Union law a constitutional principle.
Keywords: konstytucja V Republiki Francuskiej; Rada Konstytucyjna; prawo unijne; europejski wymiar konstytucji; European dimension of constitution; EU law; the Constitution of the 5th French Republic; the Constitutional Council